Animacy as a memory enhancer during novel word learning: evidence from orthographic and semantic memory tasks. Issue 6 (3rd July 2019) - Laurino, Julieta; Kaczer, Laura
ABSTRACT: It was previously shown that words representing living things are better remembered than those representing nonliving things. Here we address the influence of animacy on novel word memory formation in adults, dissecting its effect on semantic and orthographic learning. Participants received training on a set of new picture-name-description mappings corresponding to animate or inanimate items, simulating word learning in the first language. The integration of novel words was indexed in a semantic judgment task, performed at 30 min or 48 h after learning. Results show that novel word forms and meanings corresponding to animate items are better recalled than inanimate ones. In addition, animate items are processed faster than inanimate items in a semantic judgment task 30 min after learning, while the speed advantage is not evident in the long-term. Thus, animacy is a pervasive memory enhancer during novel word acquisition but its effects on lexical processing are short-lived.